Dietitians' Perspectives on Teaching Nutrition to Medical Students. (18th August 2017) - Burch, Emily; Crowley, Jennifer; Laur, Celia; Ray, Sumantra; Ball, Lauren
ABSTRACT: Objectives : The provision of nutrition care by health professionals can facilitate improved patient nutrition behaviors. Some education institutions include nutrition in their medical curriculum; however, doctors and medical students continue to lack competence in providing nutrition care. Dietitians are increasingly teaching nutrition to medical students, yet evidence on the topic remains anecdotal. It is important to understand the experiences of these dietitians to support improvements in undergraduate medical nutrition education. The aim of this study was to explore dietitians' perspectives of teaching nutrition to medical students. Methods : A qualitative study was conducted in collaboration with the Need for Nutrition Education/Innovation Programme (NNEdPro). Twenty-four dietitians who had provided nutrition education to medical students participated in individual semistructured interviews. Participants were from Australia ( n = 5), New Zealand ( n = 1), the United States ( n = 6), Canada ( n = 5), the United Kingdom ( n = 5), Germany ( n = 1), and Finland ( n = 1). Data analysis was conducted using a constant comparative approach to thematic analysis. Results : The dietitians expressed confidence in their ability to teach medical students and believed that they were the most appropriate professionals to administer the education. However, they were not confident that medical students graduate with sufficient nutrition competence and attributed this to poor curriculum planning for nutrition. Dietitians had access to useful resources and tools to support education, with opportunity to contribute further to integration of nutrition throughout medical curricula. Conclusion : This study suggests that dietitians are likely appropriate nutrition teachers in medical education. However, optimizing dietitians' role requires their further involvement in curriculum planning and development. Including dietitians as members of medical faculty would facilitate their input on nutrition throughout the curriculum, which could enhance the nutrition education of medical students.